Best and worst practices in management performance audits: Constructing and testing an algorithmic model - Woodside, Arch; Xia, X.; Crotts, J.; Clement, J. (2016)
The study here helps to fill the gap between the current practices of management performance audits for firms and government agencies. The study advances recent theories of program evaluation and marketing management auditing. While the application in this chapter refers to government agencies managing destination marketing programs (tourism agencies), the algorithmic model construction is applicable for all management audits. The study applies the perspectives from two streams of theory to describe five relevant activities for managing destination marketing programs: scanning, planning, implementation, assessing, and administering. The analysis proposes impact assessments to improve management performances of DMOs via checklists for assessing the quality of information in tourism-management performance audits. Checklists can serve as a management tool by management performance auditors and by DMO executives to enhance the quality in executing destination marketing programs. A meta-evaluation of 10 tourism management audit reports identifies good and bad practices. The findings indicate that substantial improvements are possible in the practice of DMO's management performance auditing, and the proposed checklist may ensure both high quality performance audit reports and improved performances in DMO practices.